Studying musical theatre theory and practice - Taylor, Millie; Symonds, Dominic (Palgrave Macmillan, 2014)
"The ideal accompaniment to any study of musical theatre, this lively textbook provides a comprehensive overview of the history, theory and practice of this popular theatre form. Bringing critical theory and musical theatre together, Millie Taylor and Dominic Symonds explore the musical stage from a broad range of theoretical perspectives, including narrative theory, orientalism, gender theory and globalization.Focusing on opera as well as musical theatre, Studying Musical Theatre considers dozens of diverse shows from 1607 to the present day. From Monteverdi to Mamma Mia, and from HMS Pinafore to Hedwig, this book offers an accessible and up-to-date guide to musical theatre for students, aficionados and enthusiasts alike"